Respuesta :

Answer:

Therefore,

x = -13 , y = 17 or x = 12 , y = 42

Step-by-step explanation:

First, you have to form equation in terms of x and y. With the given informations, the equations will be :

[tex]x - y = - 30 [/tex]

[tex] {x}^{2} + (y + 3) = 189[/tex]

Next, you have to solve it by substitution :

[tex]x = - 30 + y - - - (1)[/tex]

[tex] {x }^{2} + (y + 3) = 189 - - - (2)[/tex]

[tex](1)→(2)[/tex]

[tex] {( - 30 + y)}^{2} + (y + 3) = 189[/tex]

[tex]900 - 60y + {y}^{2} + y + 3 = 189[/tex]

[tex] {y}^{2} - 59y + 714 = 0[/tex]

[tex](y - 42)(y - 17) = 0[/tex]

[tex]y = 17 \: \: or \: \: 42[/tex]

[tex]sub \: \: y = 17 \: \: into \: \: (1)[/tex]

[tex]x = - 30 + 17 = - 13[/tex]

[tex]sub \: \: y = 42 \: into \: \: (1)[/tex]

[tex]x = - 30 + 42 = 12[/tex]